Mongolian-Chinese economic cooperation as an important factor in NEA economic regionalism (Journal of International Studies, 2007)
Mongolian-Chinese economic and trade relations went through a dramatic expansion in fifteen years from frozen relations during the Sino- Soviet cold war to all round partnership during 1990-2006. A number of factors contributed to this extraordinary development. Economic opening of both countries toward the end of the 1980s did change the environment between two countries. The collapse of the USSR and Mongolia's independence was embraced by the Chinese leadership when Ulaanbaatar chose a market economy as its main blueprint of the reforms.The political and economic relations between two countries went through three-phase process. The first phase of 1987-1991 was characterized by full normalization of bilateral relations. The second phase of 1991-1994 has brought the new legal basis to bilateral relations. The third phase 1994-2006 was characterized by the exchange of top level visits which projected long-term, stable relations towards the new century.